2009
DOI: 10.1097/scs.0b013e3181a289f5
|View full text |Cite
|
Sign up to set email alerts
|

Excision and "Transcutaneous" Lift in Patients With Neurofibromatosis of the Fronto-temporo-orbital and Auricular Regions

Abstract: Neurofibromatosis (NF) type 1 (von Recklinghausen disease) involves the face in up to 4% of the cases. Patients present with varying degrees of disfigurement according to the extent and location of the tumor. Many surgeons prefer multiple serial excisions, as it is almost impossible to remove the entire tumor without major extirpative surgery. However, because the "debulkings" are usually not accompanied by durable lift procedures, the skin sags again because of the gravitational effect on the remaining tumor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our patients according to the NAS score were rated average score 2.08 (±0.12), around categories II special in patients with both orbitotemporal and hemifacial lesions, while Lee et al, 2004 andNagata 2006 showed patients with NAS score to fall between category II and III [23,41,45] symmetry improvement showed average 8.90% (±) 4.89%, the mean percentage of improvement was lowest (7.9%) among patients with both orbitotemporal and hemifacial lesions, which may require reassessment for the possibility of surgical revisions.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our patients according to the NAS score were rated average score 2.08 (±0.12), around categories II special in patients with both orbitotemporal and hemifacial lesions, while Lee et al, 2004 andNagata 2006 showed patients with NAS score to fall between category II and III [23,41,45] symmetry improvement showed average 8.90% (±) 4.89%, the mean percentage of improvement was lowest (7.9%) among patients with both orbitotemporal and hemifacial lesions, which may require reassessment for the possibility of surgical revisions.…”
Section: Discussionmentioning
confidence: 54%
“…The importance of tissue Suspension was revealed by the characteristics of NF-1 as the loss of skin elasticity, skin extensibility and tumor recurrence increases the tissue volume which will all act with the gravitational force adding to the deformity, making the long term results unpredictable [45,46]. Durable tissue suspension can theoretically slow the tumor progression, as it minimize the effects of gravity on tumor tissue expansion [45]. The proline mesh was chosen for its durability and multiple strips with different vectors are used according to the facial submit suspended.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor resection is the only effective way of PNF treatment. 11 13 The aim of surgical intervention for facial disfigurement involves tumor debulking, function restoring, and cosmetic facial appearance reconstruction.…”
Section: Discussionmentioning
confidence: 99%